2020
DOI: 10.4049/jimmunol.1901317
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium yoelii Uses a TLR3-Dependent Pathway to Achieve Mammalian Host Parasitism

Abstract: Malaria is associated with complicated immunopathogenesis. In this study, we provide evidence for an unexpected role of TLR3 in promoting the establishment of Plasmodium yoelii infection through delayed clearance of parasitemia in wild type C57BL/6jRj (B6) compared with TLR3 knockout mice. In this study, we confirmed an increased expression of Tlr3, Trif, Tbk1, and Irf7/Irf3 in the liver 42 h postinfection and the initiation of an early burst of proinflammatory response such as Ifng, NF-kB, and Tnfa in B6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
(82 reference statements)
1
1
0
Order By: Relevance
“…These observations strongly suggest a link between the LAP pathway and TLR3-dependent pathway in the transfer of PbA-MVs and the induction of pro-inflammatory cytokine and chemokine responses in astrocytes from CM S mice. Therefore, a TLR3-TRIF-dependent pathway could also participate in neuroinflammation during ECM, similar to what has been reported for the intrahepatic stage [77].…”
Section: Role Of Autophagy-dependent Pmvs In CMsupporting
confidence: 83%
“…These observations strongly suggest a link between the LAP pathway and TLR3-dependent pathway in the transfer of PbA-MVs and the induction of pro-inflammatory cytokine and chemokine responses in astrocytes from CM S mice. Therefore, a TLR3-TRIF-dependent pathway could also participate in neuroinflammation during ECM, similar to what has been reported for the intrahepatic stage [77].…”
Section: Role Of Autophagy-dependent Pmvs In CMsupporting
confidence: 83%
“…The granulomas damage hepatocytes and the normal histological structure, consequently induce portal hypertension. TLR3 is involved in the host response to viral infection [ 41 ], and has a possible role during Plasmodium infection through the initiation of complex circuits and signals of the immune response [ 42 ]. In this study, gross examination of livers excised indicated that infection caused inflammatory cell infiltration that was no significant difference between WT infected and TLR3 KO infected mice.…”
Section: Discussionmentioning
confidence: 99%